Detection of Plant Genes Using a Rapid, Nonorganic DNA Purification Method. (February 2000) - Lin, J.-J.; Fleming, R.; Kuo, J.; Matthews, B.F.; Saunders, J.A.
We have developed a simple procedure for the preparation of plant genomic DNA using FTA paper. Plant leaves were crushed against FTA paper, and the genomic DNA was purified using simple, nonorganic reagents. The 18S rRNA gene and the gene encoding the ribulose-1, 5-bisphosphate carboxylase/oxygenase large subunit ( rbc L) from the chloroplast genome were detected by PCR amplification of DNA on FTA paper. DNA amplification was successful using extracts from 16 dicot and monocot plants. Studies of specific plant extracts revealed that extracts of leaf samples could be collected and stored at room temperature on FTA paper without a decrease in the DNA amplification success rate for more than a month. Both the 18S RNA gene and the rbc L gene were detected in the genomic DNA isolated from various soybean cultivars stored in this manner. Furthermore, by modestly increasing the number of cycles of DNA amplification, we were able to detect the uid A gene in transgenic tobacco and rice leaves as well as a single copy gene linked to the resistance gene of cyst nematode race 3 using genomic DNA isolated on FTA paper. These results demonstrate that genomic DNA isolated using FTA paper can be used for the detection of plant genes, from a wide range of plants with either high or low gene copy number and of either nuclear or cytoplasmic origin.